EBV Positive Gastric Carcinomas and Their Clinicopathological Characteristics - Ognjenovic, Ljubomir; Gjoshev, Stojan; Aleksandar Shumkovski; Volchevski, Goce; Trajkovski, Gjorgji; Karadzov, Zoran; Darko DJambaz; Hadzi-Manchev, Dragan; Hadzi-Manchev, Todor; Gordana, Petrushevska; Vesna, Janevska; Nikola Brzanov; et al. (ID Design 2012/DOOEL Skopje, 2018)
The understanding of the etiopathogenesis of gastric carcinoma (GC) can be a base for development of new therapeutic methods to reduce mortality and to increase survival in patients with GC. The percentage of Epstein - Barr virus (EBV) positive gastric carcinomas is uncertain, and the etiologic importance of EBV in the pathogenesis of GC has still not been elucidated.